Isolation of Staphylococcus epidermidis from inflamed upper respiratory tract of an orange-spined hairy dwarf porcupine (Sphiggurus villosus) - Fornazari, F. [UNESP] (2012)
The orange-spined hairy dwarf porcupine (Sphiggurus villosus) is a rodent species common in most parts of South America, and little is known about the pathologies that can afflict it. A specimen was delivered at the Wildlife Research and Medical Center (CEMPAS), School of Veterinary Medicine and Animal Husbandry, UNESP, Botucatu, SP, Brazil. The animal showed intense apathy, with purulent secretion in the nasal cavity and fracture of the lumbar spine. Due to the unfavorable prognosis, the porcupine was euthanized and microbiological culture of nasal discharge showed Staphylococcus epidermidis. The antimicrobial resistance test revealed sensitivity to all tested antimicrobials (ampicillin, oxacillin, tetracycline, penicillin G, neomycin, cephalexin, gentamicin, enrofloxacin, ciprofloxacin, cotrimoxazol, cefoxitin and cephalothin). This bacterium is part of the nasal flora of humans and other animals, and may cause infection under certain conditions. In the present study, the infection and colonization by S. epidermidis was the probable cause of the inflammatory process. The sensitivity to all tested antimicrobials suggests that this strain has not been previously exposed to such drugs.